2009
DOI: 10.1029/2008ja013870
|View full text |Cite
|
Sign up to set email alerts
|

A statistical study of BRIs (SMCs), isolated substorms, and individual sawtooth injections

Abstract: [1] There are many similarities and differences in the solar wind drivers during three of the main modes of convection in the magnetosphere (isolated substorms, global sawtooth oscillations, and steady magnetospheric convection (SMC) events, which we term here balanced reconnection intervals (BRI)). Thus, this investigation utilizes statistical analysis to compare the solar wind and interplanetary magnetic field (IMF) drivers and their steadiness (standard deviation divided by the mean) during these three diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
63
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(74 citation statements)
references
References 41 publications
9
63
2
Order By: Relevance
“…The SMC quartiles are much closer to the median velocity than the quartiles of other events. Similar steadiness was recently reported by (DeJong et al, 2009). Furthermore, the quartiles span a much larger range of velocities for sawtooth and storm-time events than they do for the isolated substorms and SMCs.…”
Section: Effect Of the Driving Solar Wind Electric Fieldsupporting
confidence: 86%
See 1 more Smart Citation
“…The SMC quartiles are much closer to the median velocity than the quartiles of other events. Similar steadiness was recently reported by (DeJong et al, 2009). Furthermore, the quartiles span a much larger range of velocities for sawtooth and storm-time events than they do for the isolated substorms and SMCs.…”
Section: Effect Of the Driving Solar Wind Electric Fieldsupporting
confidence: 86%
“…Steady magnetospheric convection (SMC (Sergeev et al, 1996)) events (also called convection bays (Pytte et al, 1978), continuous magnetospheric dissipation (CMD (Tanskanen et al, 2005)) events, or Balanced Reconnection Intervals (BRI (DeJong et al, 2009))) are periods during which the driving solar wind is steady and the ionospheric convection is enhanced but substorm activity is not observed (McPherron et al, 2005;Sergeev et al, 1996). The solar wind speed is typically rather low, and the magnitude of the interplanetary magnetic field (IMF) is moderate and stable.…”
Section: Introductionmentioning
confidence: 99%
“…We also find indications that the ionospheric convection pattern also remains fairly stable during SMC intervals and that the solar wind velocity was rather low for most of the SMC intervals of our dataset, generally below ∼ 400 km s −1 . The low solar wind velocity of SMCs was also found in several previous studies (O'Brien et al, 2002;DeJong et al, 2009;Huang et al, 2009;Partamies et al, 2009a, b). It is thought to be related to the lower reconnection electric field of the slower solar wind and with specific internal properties of the magnetosphere possibly regarding magnetotail convection, but a full understanding of the mechanism is still needed.…”
Section: Properties Of Smcssupporting
confidence: 84%
“…The behaviour of such a complex coupled system comprising the solar wind, the magnetosphere and the ionosphere can obviously not be reduced to just a few numbers, even though the amount of open magnetic flux and the reconnection rates are among the most important ones. This mode classification should not hide the key role of the solar wind properties in the dynamics of the magnetosphere, as has been statistically studied by DeJong et al (2009), who highlighted the importance of the IMF B z component and of the solar wind velocity, temperature and Mach number (which control the dayside reconnection rate in large measure). For example, the importance of having a low solar wind velocity for the development of the SMC mode does not appear in the present analysis.…”
Section: Intercomparison Of Magnetospheric Convection Modesmentioning
confidence: 97%
“…Although there is sporadic activity that emerges intermittently in both the inner magnetosphere and the plasma sheet, the large-scale configuration of the magnetosphere is fairly stable [Sergeev et al, 1996, and references therein]. Statistical results have shown that solar wind speed may play an important role in modulating isolated substorms, sawtooth events and SMCs, but those results are mainly focusing on solar wind-magnetosphere coupling [Partamies et al, 2009;DeJong et al, 2009]. Global MHD simulations have made progress in modeling SMCs as suggested by Raeder et al [2008] that almost all of them tend to produce SMC-like state during steady southward IMF.…”
Section: Introductionmentioning
confidence: 99%